Hot electron spectra on advanced targets in FIREX. (March 2016) - Ozaki, T.; Sunahara, A.; Shiraga, H.; Arikawa, Y.; Fujioka, S.; Sakagami, H.; Zhang, Z.; Nagatomo, H.; Johzaki, T.; Namimoto, T.; Taga, M.; Kojima, S.; et al.
Abstract: The traditional fast ignition scheme is that a compressed core created by an imploding laser is auxiliary heated and ignited by the hot electrons (produced by a short pulse laser guided through the cone and guided under-dense plasma). However sufficient heating has not be achieved because the hot electron energy is too high and dissipated in the cone, the angular divergence of the hot electron is too large, and the distance from the generation point to the core is too long. Here we clarify the problems of fast ignition by observation of the hot-electron spectra.